Antimicrobial Activity of Red Fruit (Pandanus conoideus Lam) Paste against Staphylococcus aureus and Escherichia coli in Burger Patties (Faculty of Animal Science Universitas Brawijaya, 2021)
This study aims to determine the antimicrobial activity of red fruit paste against Staphylococcus aureus FNCC-0047 and Eschericia coli FNCC-0091 by using ethanol and n-hexane as well as the total plate count value of the patty with red fruit paste added on different observations day. The concentration of paste extract for antimicrobial activity test was 6.25%, 12.5%, 25%, 50%. The calculation of the total value of the burger patty plate is calculated on the 3rd, 7th and 14th d with the red fruit paste content in the formula as much as 0%, 5%, 10%, 15%. The results showed that the fatty acids of red fruit paste were dominated by oleic acid and linoleic acid, which are unsaturated fatty acids and palmitic acid, which are saturated fatty acids. The yield of red fruit paste in n-hexane solvent was higher than ethanol solvent. There was a significant difference (P <0.05) from the use of different solvents to the mean clear zone of the two bacteria tested. The antibacterial activity shown by the ethanol extract and n-hexane extract of red fruit paste was in the inactive category at the 6.12% level, the moderate category at the 12.5% to 25% level and the strong category at the 50% level. There was a significant difference (P <0.05) from the total microbial value in each treatment where the higher the red fruit paste content in the patty, the lower the total microbial value found on each d of observation. The use of red fruit paste at a level of 10% to 15% can withstand the rate of microbial growth